Ad libitum adjustments to fluid intake during cool environmental conditions maintain hydration status during a 3-day mountain bike race. Issue 6 (6th June 2008) - Rose, S; Peters-Futre, E M
Abstract : Objective: In this study, the hydration status of amateur cyclists who voluntarily adjusted their fluid intake to environmental conditions during a 3-day, 248-km mountain bike (MTB) race was assessed. Design: Prospective observational field study. Setting: Sani2C MTB Race, KwaZulu-Natal, South Africa, 2006. Participants: 18 randomly selected amateur, male MTB cyclists. Main outcome measures: Reported usual fluid intake, environmental conditions, voluntary fluid intake, urine voided, changes in body mass, serum osmolality (SO), sodium concentration [Na + ] and urinary specific gravity (Usg) during each stage (S). Results: Dry bulb temperature (adjusted for windchill) ranged from 6° to 21.4°C during S1, S2 and S3. While 77.8% (n = 14) of subjects reported a usual intake of >750 ml h −1 in previous MTB events, mean (SE) fluid intake in this race ranged from 341 (32) ml h −1 during S1 to 551 (56) ml h −1 during S3. Changes in mean body mass ranged between −0.99% and −2.02% during the three stages. Mean SO and serum [Na + ] ranged between 292 (0.73) mOsm kg −1 and 298 mOsm kg −1 and 137 (0.35) mEq and 140 (0.42) mEq, respectively, during the 3-day period, while Usg remained ≤1.025. Conclusion: Ad libitum fluid intake during the 2006 Sani2C MTB Race, which took place in unexpectedly cold environmental conditions, was substantially lower than the usual reported fluid intake of subjects. Changes in body mass, SO, serum [Na + ] and Usg were not clinically significant, indicating that an adequate hydration status was maintained during the multiday MTB cycle race.